2017
DOI: 10.1016/j.neulet.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactamase inhibitor, clavulanic acid, attenuates ethanol intake and increases glial glutamate transporters expression in alcohol preferring rats

Abstract: Studies from our laboratory showed that upregulation of glutamate transporter 1 (GLT-1) and cystine-glutamate exchanger (xCT) expression with ceftriaxone, β-lactam antibiotic, in the brain was associated with attenuation of ethanol consumption. In this study, we tested clavulanic acid, which is another β-lactam compound with negligible antimicrobial activity, on ethanol consumption and expression of GLT-1, xCT and glutamate aspartate transporter (GLAST) in male alcohol-preferring (P) rats. Clavulanic acid has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
(73 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, our laboratory reported that AMP treatment for five days attenuated ethanol drinking behavior in P rats, an effect that was associated with upregulation of GLT-1 expression in the Acb [11]. In addition, β-lactamase inhibitors, clavulanic acid and SUL, showed ability to upregulate GLT-1 expression in rats [15,16,68]. In the present study, we found that nine weeks of ethanol consumption reduced the expression of GLT-1 in the AcbSh, but not in the AcbCo, and that combination of AMP and SUL attenuated this effect.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, our laboratory reported that AMP treatment for five days attenuated ethanol drinking behavior in P rats, an effect that was associated with upregulation of GLT-1 expression in the Acb [11]. In addition, β-lactamase inhibitors, clavulanic acid and SUL, showed ability to upregulate GLT-1 expression in rats [15,16,68]. In the present study, we found that nine weeks of ethanol consumption reduced the expression of GLT-1 in the AcbSh, but not in the AcbCo, and that combination of AMP and SUL attenuated this effect.…”
Section: Discussionmentioning
confidence: 94%
“…It is important to note that β-lactam antibiotics (e.g., ceftriaxone and ampicillin, AMP) increased GLT-1 expression in the Acb and attenuated ethanol-drinking behaviors [11][12][13][14]. Additionally, a β-lactamase inhibitor, clavulanic acid, decreased ethanol and cocaine-seeking behaviors, and increased the expression of GLT-1 in the Acb [15,16]. The increase in the synaptic glutamate concentrations is associated with alteration in certain glutamate receptors expression [17] as well as neuroinflammation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid and its derivatives have proven a powerful antioxidant activity in response to free radicals, acting synergistically with other antioxidants. Due to its structure, ferulic acid presents the ability to interrupt the propagation of free radical chain reactions, provide attack sites for free radicals and ensure protection against lipid peroxidation [8,9,17,18]. On the other hand, the β-lactam heterocycles are substances which drew attention and interest of scientists for their potent antibacterial activity [1].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, given that the ability of β‐lactam antibiotics to induce EAAT2/GLT‐1 expression lies in their β‐lactam ring (Rothstein et al, 2005), other nonantibiotic β‐lactam compounds could also potentially treat AUD. Indeed, clavulanic acid significantly induced EAAT2/GLT‐1 (and xCT) expression in the nucleus accumbens and decreased EtOH intake and preference in P rats using a 2‐bottle choice paradigm (Hakami and Sari, 2017). Given its lack of antibiotic activity and ability to penetrate the blood–brain barrier, clavulanic acid could provide a superior treatment option for AUD over the other β‐lactam antibiotics explored.…”
Section: Glutamate Transportersmentioning
confidence: 99%